Evaluasi Pendidikan Karakter: Mengukur Pengembangan Moral dan Etika dalam Pendidikan - Ina Magdalena; Pipin Rismawati; Roselana Ardani; Vhaliesca Daffah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
Over the past 10 years, character education planning has been implemented in schools. However, the actual outcomes of its implementation remain uncertain, necessitating an identification of the issues surrounding educational evaluation in schools. This article takes a descriptive approach, encompassing methods for identifying and evaluating students' learning achievements within the school context. The objective of this research is to discover the strengths and weaknesses of various assessment methods, including essay tests, objective tests, and subjective tests. The curriculum, implementation of teaching, learning resources, and educational partners in character education have also been extensively examined. Field experiences indicate that teachers face difficulties in integrating character education across all subjects, particularly when it comes to formative evaluation. Formative evaluation is employed by teachers during the learning process to determine students' attained competencies and identify gaps between their competencies and the required standards. This information is utilized by teachers to plan subsequent lessons and enhance students' learning outcomes.